Paradigma Pendidikan Islam Dalam Penguatan Karakter Peserta Didik Berbasis Hadits Kontekstual - Intan Juwita, Ajeng; Teten Saptul Jannah, Ayi; Mardiyah, Diyah (Addabani: Interdisciplinary Journal of Islamic Education, 2026)
Islamic education aims to develop individuals intellectually, spiritually, and morally. However, contemporary practices often prioritize cognitive achievement, limiting value internalization. This study proposes a contextual hadith-based education model as an integrative approach to character formation. Using qualitative library research, this study analyzes literature on hadith studies, Islamic educational philosophy, character education, and reflective learning theories. Data were examined through content analysis to construct a conceptual framework. The findings reveal three main pillars: the prophetic teacher as a moral transformation agent, an ethical-integrative curriculum embedding hadith values across subjects, and reflective-transformative learning encouraging dialogue and experiential reflection. Hadith is positioned not only as a normative source but also as contextual guidance relevant to digital and global challenges. This model contributes to developing an integrative, humanistic, and transformative paradigm of Islamic education aimed at holistic character formation.